Comparison of Earnings Management Before and After PSAK 69 in Agricultural Companies: A Review Islamic Perspective - Adelya, Nurrizqiani; Badru, Anang; Kurniawan, Agus (Universitas Islam Negeri Raden Intan Lampung, 2024)
The objective of this study is to compare the average earnings management of agricultural companies listed on the Indonesia Stock Exchange before and after the implementation of PSAK 69. This research employs a quantitative comparative approach, utilizing secondary data in the form of annual reports from 2014 to 2021. The sampling technique applied is purposive sampling, resulting in a sample of 13 agricultural companies. Hypothesis testing begins with a normality test (One Sample Kolmogorov-Smirnov), followed by the Wilcoxon Signed Rank Test, with data analyzed using IBM SPSS Statistics 25 software. The findings indicate that there is no significant difference in the average earnings management of agricultural companies listed on the Indonesia Stock Exchange before and after the adoption of PSAK 69. The implementation of PSAK 69 does not have a direct impact on earnings quality. However, it is important to note that sound accounting standards influence the quality of financial reports produced, ensuring that these reports meet essential quality criteria such as relevance, reliability, comparability, and consistency. This study contributes to the understanding of the effects of accounting standards on earnings management practices within the agricultural sector, highlighting the need for continuous evaluation of accounting regulations to enhance financial reporting quality. Limitations of this research include the restricted sample size and the focus on a specific sector, suggesting avenues for future research to explore broader implications across different industries.